TOKCER BANTALAN : Tongkat Cerdas Alat Bantu Jalan Penyandang Tunanetra Menggunakan Arduino Mega 2560 dengan Sensor Ultrasonic HC SR-04 dan Water Level - Ririn Solekha; Maimun Zaki; Laila Aida Fatimah; Rahmat Hidayat (Sultan Publisher, 2023)
Technology can be used in various fields that can support research, of course the results of this research can be useful and beneficial as a form of community service. Even today, technology plays a role in helping people with special needs (disabilities) experience difficulties. . One example is blind people who experience difficulties due to limited vision so that sticks are used as a solution to be used as walking aids for people with disabilities in facilitating their daily activities. Therefore, the authors designed a tool called